Knowledge and Attitude of Dental Students and Recent Dental Graduates Towards Dental Pulp Stem Cells in Iran - Abedi, Pouya; Hakimi , Hamid; Ahmadinia , Hassan; Rafiei , Mehrad; Motie , Parisa (Journal of Dental School, 2022)
Objectives Considering the growing knowledge about stem cells and the role of cell-based therapies in the future, dentists should have adequate knowledge about oral stem cell sources and their applications in dentistry. The present study assessed the knowledge and attitude of dental students and recent dental graduates towards dental pulp stem cells (DPSCs) in Iran. Methods This descriptive cross-sectional study was performed in 2021 on 175 participants, including 86 dental students and 89 recent dental graduates from the Dental School of Rafsanjan University of Medical Sciences (RUMS), Rafsanjan, Iran and Dental School of Shahid Beheshti University of Medical Sciences (SBMU), Tehran, Iran. A researcher-designed questionnaire was used to collect data. The validity and reliability of the questionnaire were assessed. The data were analyzed by SPSS version 21 using the Kolmogorov-Smirnov test, independent t-test, and ANOVA. Results The mean knowledge and attitude scores of the participants were 66.16±8.51% and 68.65±11.87%, respectively. The mean attitude score was significantly correlated with “interest in participating in the courses related to stem cells” and “scientific journal review rate”. The level of knowledge of the participants from SBMU was significantly higher than that of participants from RUMS (P<0.05). Other variables did not had a significant effect on the mean score of knowledge or attitude (P>0.05). Conclusion Dental students had a positive attitude towards the application of stem cells; however, their knowledge was inadequate. Therefore, some appropriate measures must be adopted to enhance the knowledge of dental students about DPSCs, especially in universities with lower ranks.